RANCANG BANGUN SISTEM ADMINISTRASI DESA BERBASIS ANDROID DI KANTOR KEPALA DESA KERAMAT JAYA KABUPATEN MAJALENGKA - Nurmalasari, Yuli; Sujadi, Harun (Universitas Majalengka, 2019)
village administration in the sacred village of Jaya sub-district of Malausma Majalengka Regency is still running manually, that is data management is still recorded in the book not computerized. Based on the problem above, an Android-based village administration application is created by managing computerized and stored data. The methodology used is RUP (Rational Unified Process). the results of this development of this system in the form of incoming letters, outgoing letters, permission letters, and asset assets